2018
DOI: 10.1080/17435390.2018.1451567
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the in vitro genotoxicity of TiO2 nanoparticles in a regulatory context

Abstract: A review of in vitro genotoxicity studies on titanium dioxide nanoparticles (TiO-NPs) published between 2010 and 2016 was performed by France in the framework of the CLP Regulation 1272/2008/EC. Neither the few in vivo studies of low quality nor the larger number of acceptable in vitro studies available for genotoxicity allowed France to conclude on the genotoxicity of TiO-NPs. Based on this work, it was decided to compare the acceptable in vitro studies to understand the reasons for the diverging results obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 193 publications
0
52
0
Order By: Relevance
“…Recently, we reported that TiO 2 NPs have no genotoxic effects in the liver and erythrocytes when intravenously injected into gpt delta mice [17], but there are still reports about their positive effect [18,19]. Thus, the genotoxicity of TiO 2 NPs remains unclear [20,21]. TiO 2 NPs in the rodent bloodstream are translocated to the liver and remain in the tissue long-term [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that TiO 2 NPs have no genotoxic effects in the liver and erythrocytes when intravenously injected into gpt delta mice [17], but there are still reports about their positive effect [18,19]. Thus, the genotoxicity of TiO 2 NPs remains unclear [20,21]. TiO 2 NPs in the rodent bloodstream are translocated to the liver and remain in the tissue long-term [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…ANSES, however, supported the conclusions stated by Charles et al (2018) and recommended new in vivo genotoxicity data to be generated.…”
Section: Efsa Assessmentmentioning
confidence: 80%
“…The new in vitro studies identified and assessed by ANSES in the current opinion do not call into question the outcome of the review by Charles et al (2018).…”
Section: Anses Opinion April 2019mentioning
confidence: 90%
“…The challenge in interpretation of in vitro genotoxicity results was recently elaborated by Charles et al (2018). The challenge in interpretation of in vitro genotoxicity results was recently elaborated by Charles et al (2018).…”
Section: Differing Opinions During Classification Processmentioning
confidence: 99%
“…In the present case of TiO 2 classification, ANSES and RAC arrived at different conclusions on the basis of genotoxicity assessments. The challenge in interpretation of in vitro genotoxicity results was recently elaborated by Charles et al (2018). The study sought an explanation of why 36 studies did not lead to a clear picture on TiO 2 genotoxicity.…”
Section: Differing Opinions During Classification Processmentioning
confidence: 99%